(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Past Research studies analyzed the impact of entrepreneurship education programs and its efficiency. Oman is known as an emerging country with high unemployment among fresh graduates from educational institutions. This issue set off the policies of the Omani government to reshape the state towards a knowledge-based economy, where the main element was described as ’entrepreneur.’ The challenges facing the government is to shift students ’ attitudes towards entrepreneurship rather than jobs. This research will present the elements of the entrepreneurial intention and proposed model information system and factors that affect student perceptions of entrepreneurship education. Quantitative method used to collect data which included 325 Oman students between 20 to 40 years from private institutions. Results have shown that entrepreneurship education, experience and the external setting have an overall impact on students’ a positive outlook to entrepreneurship. In contrast, personal attributes and perceived feasibility have a real effect on unfavourable perceptions.